Respiratory Diseases in Post-9/11 Military Personnel Following Southwest Asia Deployment. Issue 5 (May 2020) - Krefft, Silpa D.; Wolff, Jenna; Zell-Baran, Lauren; Strand, Matthew; Gottschall, Eva Brigitte; Meehan, Richard; Rose, Cecile Stephanie
Abstract : Objective: Persistent respiratory symptoms following post-9/11 military deployment to Iraq and Afghanistan are well-recognized, but the spectrum of respiratory diseases remains poorly characterized. This study describes deployment-related respiratory diseases and the diagnostic utility of resting and exercise pulmonary function testing. Methods: Between 2009 and 2017, 127 consecutive military workers ("deployers") with new-onset respiratory symptoms underwent clinical evaluation. Deployment-related respiratory diseases were classified as proximal and/or distal. Using descriptive statistics and logistic regression, we analyzed lung function parameters associated with deployment-related distal lung disease (DDLD). Results: Common deployment-related respiratory diseases included asthma (31.5%), intermittent laryngeal obstruction (14.2%), rhinosinusitis (15%), and DDLD (68.5%). Decreased diffusion capacity (odds ratio [OR] = 4.6, 95% confidence interval [CI]: 1.4 to 15.1, P  = 0.01) was significantly associated with DDLD. Conclusions: A comprehensive diagnostic approach may identify a spectrum of proximal and distal respiratory diseases that can occur in symptomatic post-9/11 deployers, requiring a personalized approach to care.